2011
DOI: 10.1007/s00198-011-1807-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of undercarboxylated and carboxylated osteocalcin concentrations in type 1 diabetes

Abstract: Purpose To determine whether dysregulation of circulating concentrations of undercarboxylated osteocalcin (UC-OC) or GLA-carboxylated osteocalcin (GLA-OC) occurs in patients with type 1 diabetes, a condition of insulin deficiency without insulin resistance. Methods We measured serum concentrations of UC-OC and GLA-OC in 115 subjects with type 1 diabetes (T1D), ages 14–40 years, and in 55 age-matched healthy control subjects. Relationships between UC-OC and GLA-OC concentrations and patient characteristics (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 33 publications
0
28
0
4
Order By: Relevance
“…However, ucOC levels in patients with T1DM did not differ from those in healthy adults. ucOC levels were higher in younger subjects and correlated positively with IGF1 (64). In healthy children, higher ucOC levels were associated with higher insulin secretion (65) as well as with higher high-molecular weight adiponectin, while children with prediabetes had lower ucOC concentrations and b-cell dysfunction (66).…”
Section: Clinical Evidence From Measurement Of Ucocmentioning
confidence: 99%
“…However, ucOC levels in patients with T1DM did not differ from those in healthy adults. ucOC levels were higher in younger subjects and correlated positively with IGF1 (64). In healthy children, higher ucOC levels were associated with higher insulin secretion (65) as well as with higher high-molecular weight adiponectin, while children with prediabetes had lower ucOC concentrations and b-cell dysfunction (66).…”
Section: Clinical Evidence From Measurement Of Ucocmentioning
confidence: 99%
“…A finding of low bone formation markers in association with T1D has been reported in most [35, 38, 47•, 50, 67, 68•, 69, 70], but not all studies [29]. Results for bone resorption markers have been variable, with most studies reporting normal levels [35, 38, 50, 70, 71], and others finding lower [47•, 59•, 72], or in one case higher levels [69] in T1D participants compared to controls. A cross-sectional study in adults identified an inverse relationship between non-fasting glucose and P1NP and CTX [73], and a longitudinal study in children found an inverse relationship between HbA1c and OCN and CTX [67], suggesting a negative effect of hyperglycemia on bone turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Because IGF-I mediates a number of osteo-promoting actions within skeletal tissues [4], deficiencies of IGF-I could contribute to skeletal abnormalities observed in T1D. IGF-I concentrations correlate positively with serum markers of bone formation in humans with T1D and IGF-I concentrations are lowest in osteopenic diabetic individuals compared to those without osteopenia [57]. Nevertheless, the role that IGF-I may play in the pathogenesis and/or prevention of T1D skeletal deficits has not been fully established.…”
Section: 1 Introductionmentioning
confidence: 99%